(4z-1)=3(z+2)

Simple and best practice solution for (4z-1)=3(z+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4z-1)=3(z+2) equation:


Simplifying
(4z + -1) = 3(z + 2)

Reorder the terms:
(-1 + 4z) = 3(z + 2)

Remove parenthesis around (-1 + 4z)
-1 + 4z = 3(z + 2)

Reorder the terms:
-1 + 4z = 3(2 + z)
-1 + 4z = (2 * 3 + z * 3)
-1 + 4z = (6 + 3z)

Solving
-1 + 4z = 6 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-1 + 4z + -3z = 6 + 3z + -3z

Combine like terms: 4z + -3z = 1z
-1 + 1z = 6 + 3z + -3z

Combine like terms: 3z + -3z = 0
-1 + 1z = 6 + 0
-1 + 1z = 6

Add '1' to each side of the equation.
-1 + 1 + 1z = 6 + 1

Combine like terms: -1 + 1 = 0
0 + 1z = 6 + 1
1z = 6 + 1

Combine like terms: 6 + 1 = 7
1z = 7

Divide each side by '1'.
z = 7

Simplifying
z = 7

See similar equations:

| 12a+3+3a+2= | | -x^2+32x-220=0 | | -1/6x-3/2=3/2 | | 0.5(4y+8)+0.5(2y+6)= | | 14x+4x-x=-7 | | 3(1.5x+8)+4(x+3)= | | 1/2(6x-2)=1/3(x-9) | | 5m+10cm= | | 4(2x-2.3)=5x-9.2 | | y-7/2=-9/4 | | -0.9+6.14=-0.4x+6.64 | | 8+4ln(x-5)=20 | | 3.4x-21=2.4x+4 | | 5/9(F-32)13 | | 5(3d+1)+3(2d+2)= | | 4(x+2)+2(3x+4)= | | 4x-7x+9x=100 | | 2x^2+1=25 | | 6y-4+4x+10=180 | | X^2-5x-414=0 | | -5(40-7)=-6n-35 | | -4(2x+7)=44 | | 5x-6=3x-3 | | 3/2*8/3*15/4 | | (1.5x+7)+5(0.1x+1)= | | X^2+5x-414=0 | | 4(d-4)+3(d+7)= | | 6h+5=53 | | Y-(-3)=-1.5 | | x+4=-3(5-x)+3(4x-2) | | 2log(x+2)-log(5x+6)=0 | | 2/5=3.8/x |

Equations solver categories